Tissue-Resident Memory T Cells in Antifungal Immunity - LeibundGut-Landmann, Salomé (Frontiers in Immunology, 2021)
Fungi are an integral part of the mammalian microbiota colonizing most if not all mucosal surfaces and the skin. Maintaining stable colonization on these surfaces is critical for preventing fungal dysbiosis and infection, which in some cases can lead to life threatening consequences. The epithelial barriers are protected by T cells and additional controlling immune mechanisms. Noncirculating memory T cells that reside stably in barrier tissues play an important role for host protection from commensals and recurrent pathogens due to their fast response and local activity, which provides them a strategic advantage. So far, only a few specific examples of tissue resident memory T cells (TRMs) that act against fungi have been reported. This review provides an overview of the characteristics and functional attributes of TRMs that have been established based on human and mouse studies with various microbes. It highlights what is currently known about fungi specific TRMs mediating immunosurveillance, how they have been targeted in preclinical vaccination approaches and how they can promote immunopathology, if not controlled. A better appreciation of the host protective and damaging roles of TRMs might accelerate the development of novel tissue specific preventive strategies against fungal infections and fungi-driven immunopathologies.